Solvent Engineering of Ionic Liquids for Stable and Efficient Perovskite Solar Cells. Issue 1 (8th January 2023) - Wang, Fei; Zhou, Xianfang; Liang, Xiao; Duan, Dawei; Ge, Chuang-Ye; Lin, Haoran; Zhu, Quanyao; Li, Liang; Hu, Hanlin
Abstract : Perovskite Photovoltaics In article number 2200140, Hanlin Hu, Liang Li, Quanyao Zhu, and co‐workers provide an overview, of the categorization and applications of ionic liquids (ILs) as pure processing solvents in perovskite photovoltaics. The employment and significance of ILs as neutral solvents in the perovskite precursor solution, as well as the implications on stability and photovoltaic performance are summarized.